Nonsurgical endodontic management of dens invaginatus: A report of two cases - Hasna, Amjad Abu [UNESP]; de Toledo Ungaro, Daniela Maria [UNESP]; de Melo, Allana Agnes Pereira [UNESP]; Yui, Karen Cristina Kazue [UNESP]; da Silva, Eduardo Galera [UNESP]; Martinho, Frederico Canato; Gomes, Ana Paula Martins [UNESP] (F1000Research, 2019)
Dens invaginatus is a malformation affecting mainly the superior lateral incisors. It is defined as an infolding of the crown hard tissues, including the enamel and dentin, and can extend up to the root apex. Root canal treatment of this abnormality is considered difficult due to the complex anatomy presented by these teeth. This case series presents nonsurgical endodontic treatment in two cases of dens invaginatus (type II and III) in maxillary lateral incisors. This nonsurgical or conventional endodontic treatment results in healing of the periapical lesions associated with both cases, with no need for extra intervention e.g. surgical or invasive management. The manual instrumentation associated with sodium hypochlorite and calcium hydroxide were able to completely heal the lesions. Radiographic exams were carried out to control and asses the healing. Nonsurgical treatment was successful in both cases with adequate repair after a 6-year follow-up with radiographic and tomographic assessments.
Keywords: Dens invaginatus; Follow-up; Root canal treatment